Noscomial Acinetobacter infections in intensive care unit (2013)
Acinetobacter plays an important role in the infection of patients admitted to hospitals. Acinetobacter are free living gram-negative coccobacilli that emerge as significant nosocomial pathogens in the hospital setting and are responsible for intermittent outbreaks in the Intensive Care Unit. The aim of this study was to determine the prevalence of Acinetobacter in patients admitted into the Intensive Care Unit and determine their role in infections in the ICU. A total of one hundred patients were recruited for the study, catheter specimen urine, tracheal aspirate and blood culture were collected aseptically from the patients. The specimens were cultured on blood and MacConkey and the organisms identified using Microbact 12E (0xoid). The Plasmid analysis was done using the TENS miniprep method. Fourteen (14%) of the 100 patients recruited into the study, developed Acinetobacter infection. Acinetobacter spp constituted 9% of the total number of isolates. Twelve (86%) of the isolates were recovered from tracheal aspirate, 1(7%) from urine and 1(7%) from blood. All of the isolates harbor plasmids of varying molecular sizes. Ten of the fourteen Acinetobacter were isolated at about the same period of time in the ICU with 6(42.7%) having plasmid size in the 23.1kb band and all showed similar pattern revealing that the isolates exhibit some relatedness. The clonal nature of the isolates suggest that strict infection control practices must be adopted in ICU, also an antibiotic policy must be developed for the ICU to prevent abuse of antibiotics that may lead to selection of resistant bacteria.